FAKTOR PROGNOSIS: TUMOR OTAK PRIMER DAN SEKUNDER - Dananjoyo, Kusumo; Malueka, Rusdy Ghazali; Briliansy (Majalah Kedokteran Neurosains Perhimpunan Dokter Spesialis Saraf Indonesia, 2025)
Brain tumors represent a heterogeneous group of diseases with considerable biological and clinical variability, resulting in highly diverse prognoses even among patients with similar histopathological diagnoses. Accurate prognostic assessment plays a crucial role in guiding appropriate treatment selection, preventing overtreatment or undertreatment, and facilitating the planning of palliative and supportive care. Multiple prognostic factors influence patient survival, including clinical variables (age, functional status, tumor location, and extent of resection), radiological features (tumor size, peritumoral edema, enhancement patterns, diffusion and perfusion MRI), histopathological findings (WHO grade, histological subtype), and biomolecular markers (IDH mutation, 1p/19q co-deletion, MGMT promoter methylation, ATRX loss, EGFR amplification, TERT mutation). In high-grade gliomas, IDH mutation, MGMT methylation, and 1p/19q co-deletion are associated with improved prognosis, while microRNAs such as miR-15b and miR-221 are increasingly recognized as potential prognostic biomarkers. In meningiomas, gross total resection (Simpson grade 1–3) is associated with lower recurrence rates compared to subtotal resection, whereas in brain metastases prognosis is determined by age, Karnofsky Performance Status, number of lesions, and control of the primary tumor. Thus, prognostic estimation extends beyond survival figures, serving as a critical foundation for individualized treatment planning, resource allocation, and effective communication with patients and families, ultimately supporting personalized therapy to enhance quality of life and patient satisfaction. Keywords: Prognostic factors, glioma, meningioma, brain metastases, brain tumors